Pesquisa de causas genéticas do câncer não medular familial da tireoide - Rodrigues, Mariana Teixeira [UNIFESP] (2017)
Non-medullary thyroid carcinoma (NMTC) is a neoplasm that originates in follicular thyroid cells, corresponds to 90-95% of thyroid cancers, and 3 to 6% are familial cases (FNMTC). The FNMTC is considered syndromic when the patients present clinical picture of Mendelian tumor syndromes with low preponderance of thyroid tumors. Some syndromes are well characterized, such as Cowden's Syndrome, Gardner's Syndrome, Carney's Complex, and Werner's Syndrome, although clinical manifestations may vary from family to family. Mutations in different genes have already been associated with these syndromes and in 80-85% cases of Cowden's Syndrome, mutations in the PTEN gene have been identified (10q23.3). This work aimed to investigate genetic alterations involved in the clinical picture of a family with suspicious of syndromic FNMTC. The study included a family from Piauí with 13 members diagnosed with thyroid, skin, breast, lung, gastric, oral or bone cancer. Although it does not clearly fit into any of the FNMTC syndromes, the possibility of being a Cowden's Syndrome was not ruled out. Therefore, mutations in the exons and promoter of PTEN gene sequence were first screened using Sanger's sequencing of peripheral blood DNA from a patient with thyroid cancer. Six variants previously described in the unaffected population were identified and, therefore, were not related to the disease. Subsequently, new generation sequencing of the genome coding regions and UTRs regions (expanded WES, 71mb per sample) of three cancer patients was carried out, for which the SureSelectXT Human All Exon V6 + UTR Capture Library kit was used (Agilent) and the Illumina® NextSeq™ 500 platform. WES generated between 3.69Gb and 4.85Gb of data per sample. Approximately 85 million bases were sequenced for each patient and more than 60% of bases had coverage greater than or equal to 30x. After several bioinformatics analyzes, five SNVs with high potential to be mutations, present in the three patients, were absent in the database and in 18 Brazilian individuals not affected by thyroid cancer and considered pathogenic by prediction programs. Only one of the variants (c.50A> C in the MSN gene) seemed to segregate with the disease, was present in other affected patients and in two asymptomatic individuals. However, it was discarded because the alteration located in X chromosome could not be inherited from the transmitting father with lung cancer to a male asymptomatic carrier. No insertions or deletions (indels) related to the FNMTC family were found. Therefore, it was ruled out the possibility of being a case of CNMT syndromic, raising the hypothesis of being a case of familial cancer or family group, characterized by the lack of inheritance pattern, the presence of a high number of individuals with sporadic tumors, presence of various types of tumors and age of onset of the disease like sporadic cases. We conclude, therefore, that this family could be classified as a case of familial and non-hereditary cancer. However, studies of other regions of the genome not assessed by expanded whole exome sequencing or the use of alternatives pipelines could suggest a genetic predisposition to cancer.